1969
DOI: 10.1055/s-0028-1091861
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Behavioural Maturation in Newborn Infants of Diabetic Mothers1– Part I: Nerve conduction and EEG patterns2

Abstract: behavioural maturation in newborn infants of diabetic mothers. Part I : Nerve conduction and EEG patterns. Neuropadiatric 1: 24-35 (1969). Infants of d i a b e~i c mothers were compared with normal neonates of the same menstrual age in order u, deterrnhe their dogree of maturity by means of neurophysiological parameters, i.e. nerve conduction velocity indicating peripheral nerve myel.inisation, 2nd EEG patterns indicating cortical, dendritic, synaptic activity. Nerve conduction velocities were found t o be alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1970
1970
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…More than 27 years ago, Shulte et al 14studied the neurological development of newborn infants born to diabetic mothers, compared with that in control newborn infants. They found longer rapid eye movement (REM) sleep in newborn infants of diabetic mothers.…”
mentioning
confidence: 99%
“…More than 27 years ago, Shulte et al 14studied the neurological development of newborn infants born to diabetic mothers, compared with that in control newborn infants. They found longer rapid eye movement (REM) sleep in newborn infants of diabetic mothers.…”
mentioning
confidence: 99%
“…They suggested that antepartum maternal glucose metabolism might have an impact on the developing brain in utero. Shulte et al 14 reported more immature electroencephalography patterns in infants of mothers with diabetes as compared to control infants, suggesting a delayed neural maturation. Priestly 15 in an early study of infants of mothers with diabetes reported that, compared with control infants, infants of mothers with diabetes showed significantly less mature Moro (P Ͻ .001) and grasptraction responses (P Ͻ .05).…”
Section: Discussionmentioning
confidence: 96%
“…N-REM sleep or quiet sleep is regulated from the medullary activating system with concomitant inhibition of the pontine and mesencephalic systems. In this state, the medulla is definitely controlled by the cortex and other higher centers ( JOUVET 1967, LIND~LEY 1960, MAGOUN 1963, M o~u z z r and MAGOUN 1949, SKINNER, LINDSLEY 1967, STER-MAN and CLEMENTE 1962. Thus, the various states of sleep and arousal have in common the brain stem reticular system, although main centers of control are at different levels in the brain stem.…”
Section: Sleep Studies For the Neurological Assessment O F The N E W mentioning
confidence: 99%